2016
DOI: 10.17509/edusentris.v3i3.233
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Kognitif Dan Kreativitas Siswa Pada Topik Biogas

Abstract: Penelitian ini bertujuan untuk mengidentifikasi dampak PBL terhadap peningkatan kemampuan kognitif dan kreativitas peserta didik. Metode penelitian yang digunakan adalah kuasi eksperimen One Group Pretest-Postest Design, dengan subjek penelitian 38 orang peserta didik kelas XI di SMAN 24 Kota Bandung. Peserta didik dibagi dalam tiga kategori kelompok kemampuan yaitu tinggi, sedang dan rendah. Peningkatan hasil belajar dihitung menggunakan N-gain. Hasil penelitian menunjukan bahwa model pembelajaran ini dapat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The average percentage of the problem-based learning model stages that students received from six groups can be seen in Figure 3. Other studies that use the problem-based learning model emphasize that the problem-based learning model requires students to study actively independently in solving problems, analyzing problems, learning issues, discovery, and reporting experimental results, presentation of solutions, reflection, making conclusions and evaluations (Fahruroji, Kurnia, & Rosbiono, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The average percentage of the problem-based learning model stages that students received from six groups can be seen in Figure 3. Other studies that use the problem-based learning model emphasize that the problem-based learning model requires students to study actively independently in solving problems, analyzing problems, learning issues, discovery, and reporting experimental results, presentation of solutions, reflection, making conclusions and evaluations (Fahruroji, Kurnia, & Rosbiono, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Model problem-based learning merupakan model pembelajaran yang saat ini digunakan dalam kurikulum 2013 agar dapat meyiapkan peserta didik berpikir memecahkan permasalahan dalam kehidupan dunia nyata [14], [15]. Model problem-based learning menjadi tuntutan kurikulum melalui konsep 'learning by doing', yang menciptakan peluang bagi peserta didik untuk belajar dengan mengalami proses penyelesaian masalah.…”
Section: B Pembahasanunclassified
“…Several previous studies that have been conducted using a problem-based learning model have shown good results, which can improve creative thinking skills, cognitive abilities, conceptual mastery, critical thinking, and student academic achievement (Ulger, & Imer, 2013;Birgili, 2015;Fahruroji. et al, 2016;Efwinda & Sopandi, 2016;Wahyu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%